Studies of carbon monoxide oxidation at ambient conditions - Rani, Radha; R, Prasad (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Carbon monoxide (CO) oxidation was studied at ambient condition over hopcalite (CuMn2O2) based catalyst. The catalysts were prepared by co- precipitation method. The prepared hopcalite based catalysts, Cu-Mn-Co catalyst, Cu-Mn-Cu catalyst, Cu-Mn-Ce catalyst were examined for oxidation of CO in fixed bed tubular flow reactor. The CO is generally present at lower temperature, as it is a result of the incomplete combustion of hydrocarbons. By observation it was found that the amount of Carbon dioxide was increasing with temperature in outlet gases. Among various catalysts studied, Cerium promoted Hopcalite showed maximum catalytic activity for CO oxidation at ambient condition. The conversion of CO over Cu-Mn-Ce was started at room temperature and gives 100% CO conversion in 75 minutes. Thus, it can be concluded that the copper based catalyst would be an attractive alternative to presently used noble metals catalyst for oxidation of CO at ambient condition. The prepared hopcalite based catalysts, are low cost and resistant to moisture. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->